1995
DOI: 10.1046/j.1365-313x.1995.08020257.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple phosphoinositide‐specific phospholipases C in oat roots: characterization and partial purification

Abstract: SummaryPhosphoinositide-specific phospholipases C are critical enzymes in the transduction of hormonal and environmental signals into animal cells. Several different isozymes of phospholipese C are known in mammalian systems which differ in their expression and regulation. Elucidation of the regulation of these phospholipases C has greatly advanced our understanding of the control of mammalian cell growth and development. Plant cells, too, contain phospholipeses C specific for phosphoinositides, and there is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…We report here a kinetic study of the partially purified, membrane-associated enzyme using different approaches. Few reports regarding the biochemical characterization of plant PLC are available (Tate et al, 1989;Melin et al, 1992;Pical et al, 1992;Yotsushima et al, 1992Yotsushima et al, , 1993Hirayama et al, 1995;Huang et al, 1995;Shi et al, 1995;Kopka et al, 1998). To our knowledge, this is the first report in which different assays were used to characterize this enzyme in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report here a kinetic study of the partially purified, membrane-associated enzyme using different approaches. Few reports regarding the biochemical characterization of plant PLC are available (Tate et al, 1989;Melin et al, 1992;Pical et al, 1992;Yotsushima et al, 1992Yotsushima et al, , 1993Hirayama et al, 1995;Huang et al, 1995;Shi et al, 1995;Kopka et al, 1998). To our knowledge, this is the first report in which different assays were used to characterize this enzyme in plants.…”
Section: Discussionmentioning
confidence: 99%
“…PLC is a family of isoenzymes that has been classified into three groups: ␤, ␥, and ␦ (Rhee and Bae, 1997). In plants several studies have reported the biochemical presence of this enzyme (McMurray and Irvine, 1988;Tate et al, 1989;Melin et al, 1992;Pical et al, 1992;Yotsushima et al, 1992Yotsushima et al, , 1993Huang et al, 1995;De Los Santos-Briones et al, 1997). Different genes for PLC have also been cloned (Hirayama et al, 1995(Hirayama et al, , 1997Shi et al, 1995;Yamamoto et al, 1995;Kopka et al, 1998), all of them resembling the ␦ type.…”
Section: Camentioning
confidence: 99%
“…TCA was removed, the pH was adjusted to 8.0, and the sample was concentrated 2-fold by evaporation under nitrogen and reconstitution in H,O. Receptor-binding activity was assayed by the usual method, and hydrolysis of added [3H]Ins(1,4,5)P3 was monitored by scintillation counting following chromatographic separation of [3H]Ins(1,4,5)P3 from [3H]Ins(1, 4)P2 on Amiprep trimethylaminopropyl SAX minicolumns (Amersham) as described by Huang et al (1995).…”
mentioning
confidence: 99%
“…Phospholipase C assay PLC activity was assayed by a modification of the method of Huang et al (1995). From 1.0·10 6 to 1.5·10 6 cells were collected by centrifuging at 20 g for 10 min.…”
Section: Scoring Tracheary Elementsmentioning
confidence: 99%